Knowledge and practices about vocal hygiene among speech-language pathologists in India - Anubhuti Jain; Divya Seth; Dhanshree R. Gunjawate (PLoS ONE, 2025)
Background The objective of the present study was to explore the knowledge and practices about vocal hygiene among speech language pathologists in India. Methods An online survey was conducted to explore the knowledge and practices about vocal hygiene among speech language pathologists in India. A questionnaire was developed based on expert opinion and literature and included questions on demographic details, vocal hygiene knowledge and practices. Descriptive statistics was used to summarize continuous variables, and discrete variables were analysed using frequency and percentages. Results A total of 123 responses were considered for analyses. 74.8% of the speech language pathologists self-reported of experiencing more than one vocal symptom/difficulty. The speech language pathologists displayed good knowledge of the vocal and non-vocal factors affecting voice. With respect to reported practice, speech language pathologists exhibited inconsistencies in practice. Despite being aware about the vocal hygiene practices, speech language pathologists did not consistently implement them in daily routines. Conclusion The speech language pathologists are knowledgeable about different factors that have a positive and negative influence on voice; however, they do not practice everything regularly. As SLPs play a dual role of being a professional voice user and a clinician, it is important that they practice what they teach their patient.